Meningkatkan Kemampuan Berpikir Kritis Siswa Kelas VIII Melalui Media Ular Tangga Kewarganegaraan pada Mata Pelajaran PPKn - Anggraini, Lia Audina; Rochmadi, Nur Wahyu (Universitas Negeri Malang, 2021)
This study aimed to produce appropriate, attractive, and effective learning media for Pancasila and Citizenship Education to improve students' critical thinking skills. The development procedure was carried out according to the Thiagarajan 4-D Model. The test subjects in this study were VIII grade students of the Laboratorium Malang Junior High School. Media validity was known from the results of media expert validation by 97.5 percent and material expert validation by 92.5 percent, and the attractiveness of media based on a questionnaire obtained by 90 percent. The civic ladder snake learning media was able to improve students’ critical thinking skills because the post-test results were higher than the pretest results. The critical thinking ability average of students on the large-scale test increased from 38.7 percent to 87 percent. So, there had been a significant change in students’ critical thinking skills after the implementation of the civic ladder snake learning media. The civic ladder snake learning media were valid, attractive, and able to improve students’ critical thinking skills.